Direct laser writing by two-photon polymerization as a tool for developing microenvironments for evaluation of bacterial growth - Otuka, A. J. G.; Correa, D. S.; Fontana, Carla Raquel [UNESP]; Mendonca, C. R. (Elsevier B.V., 2014)
Monitoring bacteria growth and motion in environments is fundamental to understand, for instance, how they proliferate and contaminate organism. Therefore, techniques to fabricate microenvironments for in situ and in vivo studies are interesting for that purpose. In this work we used two-photon polymerization to fabricate microenvironments and, as a proof of principle, we demonstrated the development of the bacteria ATCC 25922 Escherichia coil (E. coil) into the microstructure surroundings. Two varieties of polymeric microenvironments are presented: (i) a microenvironment doped at specific site with ciprofloxacin, an antibiotic typically used in the treatment of diseases caused by E. coil and (ii) micro-fences, which serve as traps for bacteria. These microenvironments, fabricated by two-photon polymerization, may be a potential platform for drug delivery system, by promoting or inhibiting the growth of bacteria in specific biological or synthetic sites. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Microfabrication; Two-photon polymerization; Bacterial